Fluoropyrimidine Toxicity: the Hidden Secrets of DPYD - Manolopoulos, Vangelis G.; Ragia, Georgia (Current Drug Metabolism, 2024)
Background: Fluoropyrimidine-induced toxicity is a main limitation of therapy. Currently, polymorphisms in the DPYD gene, which encodes the 5-FU activation enzyme dihydropyrimidine dehydrogenase (DPD), are used to adjust the dosage and prevent toxicity. Despite the predictive value of DPYD genotyping, a great proportion of fluoropyrimidine toxicity cannot be solely explained by DPYD variations. Objective: We herein summarize additional sources of DPD enzyme activity variability, spanning from epigenetic regulation of DPYD expression, factors potentially inducing protein modifications, as well as drug-enzyme interactions that contribute to fluoropyrimidine toxicity. Results: While seminal in vitro studies provided evidence that DPYD promoter methylation downregulates DPD expression, the association of DPYD methylation with fluoropyrimidine toxicity was not replicated in clinical studies. Different non-coding RNA molecules, such as microRNA, piwi-RNAs, circular-RNAs and long non-coding RNAs, are involved in post-transcriptional DPYD regulation. DPD protein modifications and environmental factors affecting enzyme activity may also add a proportion to the pooled variability of DPD enzyme activity. Lastly, DPD-drug interactions are common in therapeutics, with the most well-characterized paradigm the withdrawal of sorivudine due to fluoropyrimidine toxicity deaths in 5-FU treated cancer patients; a mechanism involving DPD severe inhibition. Conclusions: DPYD polymorphisms are the main source of DPD variability. A study on DPYD epigenetics (both transcriptionally and post-transcriptionally) holds promise to provide insights into molecular pathways of fluoropyrimidine toxicity. Additional post-translational DPD modifications, as well as DPD inhibition by other drugs, may explain a proportion of enzyme activity variability. Therefore, there is still a lot we can learn about the DPYD/DPD fluoropyrimidine-induced toxicity machinery.
Keywords: toxicity